Compliance Factors in Malaysian Guidelines for Hadith Authentication - Bahrudin, Mohamad Khalid (Al-Bayān, 2024)
In 2018, Ministry of Home Affairs (MOHA) of Malaysia issued the Guideline for Writing and Publishing Hadith Texts (Garis Panduan Penulisan dan Penerbitan Teks Hadith) through Hadith Review and Assessment Committee (HRAC) to ensure high-quality hadith texts. A survey of 61 industry representatives revealed a moderate compliance level with a mean score of 2.69. This study uses quantitative methods, including descriptive and inferential analysis, to identify factors influencing compliance. Ten factors were measured, such as guideline characteristics, author/editor bias, publication type, company orientation, promotional strategies, guideline producer, law enforcement impact, training, incentives, and bureaucracy. The survey instrument demonstrated high reliability (Cronbach’s Alpha = .903), and data analysis via SPSS 27 showed that most factors had high mean scores (> 3.68), except for publication type (2.21) and company orientation (2.00). Multiple regression analysis identified aggressive promotional strategies and law enforcement as significant positive influences on compliance.